Town Green area, general view of the Bacon-Prouty House, Brookline, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a house in the Town Green Area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: Town Green Area (2) Bacon-Pouty House Walking Tour 1844-1855.; Binder Number 4. Pocket Number: 17.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.